1992
DOI: 10.1111/j.1476-5381.1992.tb09056.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitric oxide in non‐adrenergic, non‐cholinergic inhibitory junction potentials in canine ileocolonic sphincter

Abstract: 1 Electrical field stimulation causes neurally-mediated relaxation of the ileocolonic sphincter that is due to activation of non-adrenergic and non-cholinergic (NANC) nerves. Recent studies have suggested that nitric oxide (NO) is the neurotransmitter that mediates relaxation. 2 Using intracellular recording techniques, we have tested whether NANC inhibitory junction potentials (ij.ps) in the canine ileocolonic sphincter are also mediated by NO. 3 Electrical field stimulation elicited excitatory and inhibitory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
5

Year Published

1993
1993
2005
2005

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 33 publications
5
26
5
Order By: Relevance
“…suggested that these changes have a myogenic origin, caused by the release of Ca 2ϩ from intracellular stores, acting on Ca 2ϩ -activated chloride channels. In contrast to several other smooth muscle tissues in which NO act as an inhibitory NANC transmitter Thornbury et al, 1991;Ward et al, 1992), the nitrergic inhibitory neurotransmission in the rabbit urethral smooth muscle seemed to be mediated through mechanisms, which do not involve membrane hyperpolarization (Waldeck et al, 1998). This contradicts results reported by Ito and Kimoto (1985), who observed inhibitory junction potentials in some registrations from rabbit urethral smooth muscle.…”
Section: B Urethracontrasting
confidence: 56%
“…suggested that these changes have a myogenic origin, caused by the release of Ca 2ϩ from intracellular stores, acting on Ca 2ϩ -activated chloride channels. In contrast to several other smooth muscle tissues in which NO act as an inhibitory NANC transmitter Thornbury et al, 1991;Ward et al, 1992), the nitrergic inhibitory neurotransmission in the rabbit urethral smooth muscle seemed to be mediated through mechanisms, which do not involve membrane hyperpolarization (Waldeck et al, 1998). This contradicts results reported by Ito and Kimoto (1985), who observed inhibitory junction potentials in some registrations from rabbit urethral smooth muscle.…”
Section: B Urethracontrasting
confidence: 56%
“…Furthermore, the involvement of other putative NANC neurotransmitters such as adenosine 5'-triphosphate, vasoactive intestinal polypeptide, GABA and 5-HT had been excluded earlier (Boeckxstaens et al, 1990b-e). Recently, electrophysiological evidence was also provided confirming the role of NO in the ileocolonic junction (Ward et al, 1992). This knowledge, together with morphological evidence demonstrating the presence of NO synthase in its myenteric neurones (unpublished observations), make the ileocolonic junction an interesting model to study possible prejunctional regulation of NO release.…”
Section: Introductionmentioning
confidence: 89%
“…In contrast, NOS inhibition reduces both the apamin-sensitive and apamin-resistant components of the i.j.p. recorded in the dog ileocolonic sphincter (Ward et al, 1992c). In addition, many gastrointestinal preparations often display a period of 'rebound' contraction and post-stimulus depolarization (PSD) following the NANC ij.p.…”
Section: Introductionmentioning
confidence: 99%